ANALISIS EFISIENSI TEKNIS DAN SUMBER INEFISIENSI USAHATANI PADI PADA LAHAN SEMPIT DI KABUPATEN BANTUL PROVINSI YOGYAKARTA - Yoshi Tri Sulistya; Lestari Rahayu Waluyati (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2019)
Technical Efficiency Analysis and IneffeciencySources of Rice Farming In Narrow Lands in Bantul District Yogyakarta Province. The increasing rice production is mostly constrained by the ever-declining agricultural land area which is mainly solved by improving productivity through efficiency. Most of the farmer's land tenure in Java is a narrow area (less than 0.5 ha). Hence, this research aimed 1) to know the level of technical efficiency, allocative and economic, and 2) to know the technical inefficiency sources of rice farming in narrow land in Jetis District, Regency of Bantul. This research applied the basic method of descriptive analytic technique. The research location was determined based on the purposive method at the location with small farming scale (land area <0.5 ha). It involved 72 farmers as the research samples with were determined by surfeited sampling technique. The resulted data were analyzed by the method of stochastic production function model with frontier 4.1 program. It was revealed that the variables affecting the increase of rice production were land area, the seed’s number and the amount of pesticides use. It resulted in the average farmers’ technical efficiency level of 0.73. A total of 63.89% farmers at the research sites were already technically efficient (efficiency level > 0.70). The sources of technical inefficiency were education, experience, number of productive family members and number of plots (plots of land). The number of family members with productive age and the number of plots will improve technical efficiency. It was revealed that the variables affecting the minimize of production cost are production quantity, fertilizer NPK phonska price, organic fertilizer, and labor wage.Keywords:rice, narrow land, rice, technical efficiency, technical inefficiencyABSTRAKPeningkatan produksi padi terkendala dengan semakin berkurangnya luas lahan pertanian, maka diupayakan dengan peningkatan produktivitas melalui efisiensi. Sebagian besar penguasaan lahan petani di pulau Jawa merupakan lahan sempit (luas kurang dari 0,5 ha). Penelitian ini bertujuan untuk 1) mengetahui tingkat efisiensi teknis, alokatif dan ekonomi, dan 2) mengetahui sumber-sumber inefisiensi teknis usahatani padi pada lahan sempit di Kecamatan Jetis, Kabupaten Bantul. Metode dasar yang digunakan dalam penelitian ini adalah metode analisis deskriptif. Penentuan lokasi penelitian secara purposive pada lokasi yang skala usahataninya kecil (lahan sempit <0,5 ha). Penentuan sampel petani dengan metode sampling jenuh sebanyak 72 petani. Metode analisis menggunakan model fungsi produksi stochastic dengan program frontier 4.1. Hasil penelitian menunjukkan bahwa variabel yang berpengaruh meningkatkan produksi yakni luas lahan dan jumlah penggunaan pestisida, sedangkan yang berpengaruh menurunkan produksi yakni jumlah benih. Rata-rata tingkat efisiensi petani sebesar 0,73. Sebanyak 63,89% petani di lokasi penelitian sudah efisien secara teknis (tingkat efisiensi teknis >0,70). Sumber-sumber inefisiensi teknis yakni pendidikan, pengalaman, jumlah anggota keluarga produktif, dan jumlah persil (petak lahan). Jumlah anggota keluarga usia produktif dan jumlah persil akan meningkatkan efisiensi teknis. Variabel yang berpengaruh meminimumkan biaya produksi adalah jumlah produksi, harga pupuk NPK phonska, pupuk organik, dan upah tenaga kerja. Kata kunci: padi, efisiensi teknis, inefisiensi teknis, lahan sempit